Microfluidics-assisted Tumor Cell Separation Approaches for Clinical Applications: An Overview on Emerging Devices - Shanehband, Nahid; Naghib, Seyed Morteza (Combinatorial Chemistry & High Throughput Screening, 2025)
Recent advances in science and technology have led to revolutions in many scientific and industrial fields. The term lab on a chip, or in other words, performing a variety of complex analyses in just a short time and a minimal space, is a term that has become very common in recent years, and what used to be a dream has now come to life in practice. In this paper, we tried to investigate a specific type of lab technology on a chip, which is, of course, one of the most common, namely the knowledge and technology of cell separation by using a microfluidic technique that can be separated based on size and deformation, adhesion and electrical properties. The tissue of the human body is degraded due to injury or aging. It is often tried to treat this tissue disorder by using drugs, but they are not always enough. Stem cell-based medicine is a novel form that promises the restoration or regeneration of tissues and functioning organs. Although many models of microfluidic systems have been designed for cell separation, choosing the appropriate device to achieve a reliable result is a challenge. Therefore, in this study, Fluorescence Activated Cell Sorting (FACS), Dielectrophoresis (DEP), Magnetic Activated Cell Sorting (MACS), and Acoustic microfluidic system are four distinct categories of active microfluidic systems explored. Also, the advantages, disadvantages, and the current status of the devices mentioned in these methods are reviewed.
Keywords: magnetic activated cell sorting